Use and Effects of Pesticides in Bagnaskali Rural Municipality-5, Darlamdanda, Palpa - Belbase, Toyanath; Gaire, Rupa (Tribhuvan Journal, 2023)
This study assessed the pesticide use practice and its health effect among the farmers of Baganaskali Rural Municipality-5 Darlamdanda, Palpa. A total of 64 respondents was selected as a sample population and data was collected through semi- structured interviews and observation. During the study, 26 types of pesticides were documented among them insecticide was the most dominant (15) followed by fungicide (6), herbicide (2), rodenticide (1) and bactericide (1). Nuvan, malathion and bullet were the most commonly used pesticides which were commonly used to control pest and to increase the yield. More than 90% farmers were suffered from pesticide related health signs and symptoms after the application of pesticide. Headache (84.38%), skin irritation (79.69%), eye problem (69.17%), muscular pain (60.94%) and dizziness (50%) were the most common health problems. Majority (95.31%) of farmers used safety measures but among them only (3.13%) farmers used whole body covering PPE. Trousers (92.19%), full sleeved clothes (82.83%) and mask (75%) were the most commonly used PPEs. Only 28.13% of farmers were participated in pesticide related training. The status of pesticide storage, handling and disposal was not found satisfactory. The farmers were in need of special attention in terms of taking safety precautions, pesticide storage, safe handling and disposal. It is recommended that the trainings regarding the use of pesticide, safe handling and use of personal protective equipment’s should be conducted with more ecofriendly farming system to raise the awareness among farmers.